Lost in Transition? Market Failure in the Implementation of the Circular Economy. A Comparative Analysis of the Netherlands and Poland - Adamus, Jagoda; Chądzyński, Jacek; Trippner‑Hrabi, Justyna (Comparative Economic Research. Central and Eastern Europe, 2024)
It is necessary for economies to transition to a circular economy (CE). What particularly inhibits the implementation of the CE in linear economies is market failures, whose theoretical principles are embedded in modern welfare economics and neoclassical economics. Market failures shape the functioning of different areas of the markets, including the allocation of and access to resources, competition, and cooperation, among others. Due to their presence in the market, opportunities for industrial symbiosis based on intersectoral cooperation and the creation of resource-efficient production systems are limited. It is crucial because the functioning of local actors within an industrial symbiosis significantly favours the promotion and development of a CE. The aim of the paper is to identify market failures that limit the implementation of CEs in traditional linear economies. The article is based on focus group interviews (FGI) conducted with four groups of stakeholders in the Netherlands and Poland: academia, society, business and the government. The main findings show that one of the greatest barriers in Poland is stakeholders’ low awareness of the CE, which influences their possibilities of cooperating and networking. Existing laws additionally limit opportunities to develop the CE. In contrast, in the Netherlands, where awareness is deeply embedded in the culture, education system and upbringing, the level of market failure is lower.